USULAN PENCATATAN KEUANGAN DIGITAL UNTUK MENINGKATKAN EFISIENSI PENDAPATAN PADA UMKM WARUNG MBAK LENY - Andana F, Mohammad Dhabith; Rafikasyah, Maulvi Akbar; Athallah Naufa, Nadindra; Ramadhan, Kanz Barra; Satryo , Izzan Zahidin; Hidayat A, Akmal Nur; Agustina, Tri Siwi; Hardi, Jhon; Fitdiarini, Noorlaily; Sudarwito, Gurun (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This research explores the role of MSMEs in improving Indonesia's socio-economic conditions, with a focus on Warung Mbak Leny in Surabaya. MSMEs play an important role in absorbing labor, increasing GDP, and helping poor families escape the cycle of poverty. Warung Mbak Leny, facilitated by the city government, provides economic opportunities for local residents and improves the standard of living of those in the poor community. Despite making positive contributions, these MSMEs face several challenges, such as a weak supply of reserve funds, unstructured financial reports, lack of digital marketing, and low product quality. This research was conducted through field observations, interviews and SWOT analysis. The research results show that MSMEs have the potential to improve Indonesia's socio-economic conditions, but need to overcome several challenges they face.